Effect of water on nanomechanics of bone is different between tension and compression. (April 2016) - Samuel, Jitin; Park, Jun-Sang; Almer, Jonathan; Wang, Xiaodu
Abstract: Water, an important constituent in bone, resides in different compartments in bone matrix and may impose significant effects on its bulk mechanical properties. However, a clear understanding of the mechanistic role of water in toughening bone is yet to emerge. To address this issue, this study used a progressive loading protocol, coupled with measurements of in situ mineral and collagen fibril deformations using synchrotron X-ray diffraction techniques. Using this unique approach, the contribution of water to the ultrastructural behavior of bone was examined by testing bone specimens in different loading modes (tension and compression) and hydration states (wet and dehydrated). The results indicated that the effect of water on the mechanical behavior of mineral and collagen phases at the ultrastructural level was loading-mode dependent and correlated with the bulk behavior of bone. Tensile loading elicited a transitional drop followed by an increase in load bearing by the mineral phase at the ultrastructural level, which was correlated with a strain hardening behavior of bone at the bulk level. Compression loading caused a continuous loss of load bearing by the mineral phase, which was reflected at the bulk level as a strain softening behavior. In addition, viscous strain relaxation and pre-strain reduction were observed in the mineral phase in the presence of water. Taken together, the results of this study suggest that water dictates the bulk behavior of bone by altering the interaction between mineral crystals and their surrounding matrix.